Peningkatan Hasil Belajar Geografi melalui Metode Sinkron dan Asinkron Berbantuan Aplikasi Google Classroom - Asih Paramayati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2021)
Geography subject matter, especially the Village and City Spatial Interaction Classroom Action Research was held with the aim of improving student learning outcomes through synchronous and asynchronous methods assisted by the Google Classroom application. The research subjects of students of XII IPS 1 SMAN 1 Banguntapan Odd Semester 2020/2021 consisted of 32 students, namely 22 girls and 10 boys. This Classroom Action Research was conducted in 2 cycles and three meetings each, each meeting lasting 75 minutes. Each meeting was conducted in a virtual or online way through synchronous and asynchronous methods using the Google Classroom application. The data collected for this study included observation data on student activity and learning outcomes of Geography, conducted from August to November 2020 with the results of the research stating that through synchronous and asynchronous methods using the Google Classroom application can have a positive influence on improving student learning outcomes on Village and City Spatial Interaction material. This can be seen from the average value in the class when the pre-action was 71.14, then in the first cycle it increased to 75.74, in the second cycle it became 76.68 and and the percentage of classical completeness can reach the target success indicator of 80%.